Alzheimer's disease susceptibility locus in CD2AP is associated with increased cerebrospinal fluid tau levels in mild cognitive impairment. (6th February 2022) - Xue, Yan-Yan; Chen, Yi-He; Lin, Rong-Rong; Huang, Hui-Fen; Wu, Zhi-Ying; Tao, Qing-Qing; ,
Highlights: There was no association between CSF Aβ1–42 level and CD2AP rs9296559 SNP in CN, MCI or AD. CC + TC genotype of rs9296559 was associated with increased CSF tau levels in MCI. CC + TC genotype of rs9296559 did not alter CSF tau levels in CN or AD. Abstract: Introduction: Rs9296559 within CD2-associated protein ( CD2AP ) has been identified as a susceptibility locus for Alzheimer's disease (AD). Recent studies indicated that CD2AP functioned as a regulator of endocytic trafficking to modulate the β-amyloid (Aβ) generation in neurons. Moreover, knockdown of cindr, the Drosophila ortholog of CD2AP, enhanced tau-induced neurodegeneration, implying CD2AP also participated in tau pathology. However, the role of rs9296559 in regulating Aβ and tau metabolism in AD was still unclear. Methods: Here, the associations of rs9296559 with CSF Aβ1–42, p-tau, and t-tau were performed using a linear regression model in a total of 543 cognitive normal (CN), mild cognitive impairment (MCI), and AD subjects from the Alzheimer's disease Neuroimaging Initiative (ADNI) cohort. The results were replicated in an independent cohort consisting of 198 Chinese subjects recruited from our hospital. Results: In the ADNI cohort, CC + TC genotypes significantly increased CSF t-tau and p-tau levels in MCI patients but did not alter CSF tau levels in AD. This association was also observed in the replication cohort. Moreover, there was no association between rs9296559 and CSF Aβ1–42 level at different disease statuses in the two cohorts. Conclusion: Our findings showed that rs9296559 was associated with higher CSF t-tau and p-tau levels in MCI, supporting that CD2AP modified AD risk by altering tau-related neurodegeneration in the early stage of the AD continuum. To the best of our knowledge, this is the first study to evaluate the association between CD2AP genotypes and AD CSF biomarkers.